THE METHODS OF STRUGGLE OF THE SOVIET SPECIAL SERVICES AGAINST THE NATIONALIST UNDERGROUND IN THE STANISLAV REGION IN THE SECOND HALF OF THE 1940S – THE FIRST HALF OF THE 1950S (Південний архів (історичні науки), 2023)
The purpose of the study is a comprehensive analysis of the key methods of the struggle of the Soviet penal authorities against the Ukrainian nationalist underground in the territory of the Stanislav region in the second half of the 1940s – the first half of the 1950s. The methodological basis of the article was the principles of objectivity, historicism, comprehensiveness, continuity, as well as a complex of general scientific and special-historical methods. Results. During the struggle against the Organization of Ukrainian Nationalists (OUN) and the Ukrainian Insurgent Army (UPA) in the territory of Stanislav region, the Soviet special services used a complex of various methods during the first post-war decade. In the context of the intelligence-operational development of the nationalist underground, a network of informants of penal authorities was actively formed; active and arrested members of the resistance movement were recruited with their further use; intelligence-combat groups were created, which committed crimes against the population under the guise of UPA fighters. A particularly significant danger for the organized underground was the fake leadership councils (provides) formed by the employees of the Ministry of State Security (MDB), which functioned practically throughout the territory of the Stanislav region, with the aim of identifying and neutralizing the real participants of the anti-Soviet resistance. Active Soviet political propaganda among the local population undermined the positions of UPA fighters, caused a significant drop in morale and will to fight among them. Work was carried out to identify the participants of the movement who were in a legal position. One of the most insidious methods used by the Soviet special services was to put pressure on the underground through their relatives – primarily wives and children. Conclusions. By the mid-1950s, the armed nationalist underground in the Stanislav region was almost completely suppressed by the efforts of the Soviet occupiers. Despite the high intensity and diversity of the punitive work of the Soviet special services in the Stanislav region, the Ukrainian national liberation movement continued to be active for a long period of time, which indicates a significant level of heroism and self-sacrifice among the insurgents.
Keywords: Ukrainian Insurgent Army (UPA), Organization of Ukrainian Nationalists (OUN), Ministry of State Security (MDB), Soviet regime, intelligence-combat groups, armed underground